The role of human papillomavirus in laryngeal cancer and recurrent respiratory papillomatosis: epidemiological and clinical aspects - D. V. Kholopov; L. V. Lyalina; E. Е. Topuzov; D. A. Alekseeva (Опухоли головы и шеи, 2024)
In the recent decade, the number of laryngeal cancer cases increased worldwide by 23 %. Currently, laryngeal cancer morbidity and associated mortality do not show statistically significant trends toward a decrease. The main risk factors for laryngeal carcinoma are smoking, alcohol consumption, human papilloma virus (HPV) infection, recurrent respiratory papillomatosis, and genetic predisposition.Aim. To evaluate the incidence and role of HPV in etiology and clinical course of laryngeal cancer and recurrent respiratory papillomatosis.Analysis of the available literature sources published in the Medline, Pubmed, and eLibrary databases was performed. The review is based on 59 of 584 identified scientific studies. Frequency of HPV detection in laryngeal cancer tumor tissue varies and is associated with the studied country’s geographical location. The incidence of these viruses in tumor tissue varies between 2.7 and 62.6 %. Genotype 16 human papilloma virus is more common in women between the ages of 31 and 40 years and is mostly located near the glottic aperture. Genotype 6 and 11 human papilloma viruses promote development of recurrent respiratory papillomatosis of the larynx and are detected in 0–87.5 % of cases. It is noted that in patients with HPV-positive neoplasms of the larynx, better response to radiation therapy and higher survival rates are observed compared to patients without the virus. In countries where national programs of vaccination against HPV infection have been implemented, a significant decrease in the incidence of recurrent respiratory papillomatosis is observed.The incidence of HPV in laryngeal cancer and recurrent respiratory papillomatosis varies. The role of these viruses in carcinogenesis has not yet been fully understood. Clinical course of HPV-associated laryngeal carcinoma is more favorable than HPV-free laryngeal carcinoma, however, this statement requires further confirmation. Evaluation of the results of programs of vaccination against HPV and their effect on recurrent respiratory papillomatosis and laryngeal cancer morbidity is important.